The relationship between intergenerational mobility and equality of opportunity - Adrian Adermon; Gunnar Brandén; Martin Nybom (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2025)
Among economists, empirical analysis of social mobility and the role of parental background is largely carried out in two separate strands of research. The intergenerational mobility literature estimates parent-child persistence in a certain outcome of interest, such as income. In contrast, the equality of opportunity literature is rooted in a normative framework, and has only more recently started generating empirical evidence. Intergenerational mobility regressions are relatively straightforward to estimate, but their normative implications are less obvious. In contrast, measures of equality of opportunity have a policy-relelvant interpretation, but are demanding in terms of data, requiring the researcher to observe a large set of determinants of socioeconomic status for large samples. But maybe the two approaches capture similar underlying dynamics? We compare the two approaches by estimating both equality of opportunity and intergenerational mobility measures - as well as sibling correlations - across 16 birth cohorts within 126 Swedish local labor markets. Using these estimates, we test to what extent the different measures correlate, resulting in insights on the plausibility of interpreting intergenerational mobility measures as informative about equality of opportunity.
Keywords: D31; J62; D63; 330; Equality of opportunity; Intergenerational mobility; Sibling correlations